2018
DOI: 10.2147/cmar.s188364
|View full text |Cite
|
Sign up to set email alerts
|

HJC0152, a novel STAT3 inhibitor with promising anti-tumor effect in gastric cancer

Abstract: BackgroundAberrant activation of the signal transducer and activator of transcription 3 (STAT3) is frequently seen in patients with gastric cancer (GC), and is generally associated with worse prognosis. HJC0152, a novel STAT3 inhibitor, has shown significant anti-tumor effects in several cancers, although its role in GC remains to be clarified.MethodsThe effect of HJC0152 on STAT3 signaling pathway and the biological behaviors of GC cells were evaluated through in vitro and/or in vivo experiments. Meanwhile, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…The signal transducer and activator of transcription protein (STAT), belongs to the family of cytoplasmic transcription factors, has been demonstrated played signi cant role in the signal transduction through multiple mechanisms [13]. Increasing evidences revealed that the STAT3 was involved in the development and progression of many cancer types through participation in a series of tumorigenic processes such as cell proliferation and survival [14]. Moreover, aberrant expression and constitutive activation of STAT3 have been detected in a variety of tumors such as the gastric cancer, breast cancer, prostate tumor, and NSCLC [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal transducer and activator of transcription protein (STAT), belongs to the family of cytoplasmic transcription factors, has been demonstrated played signi cant role in the signal transduction through multiple mechanisms [13]. Increasing evidences revealed that the STAT3 was involved in the development and progression of many cancer types through participation in a series of tumorigenic processes such as cell proliferation and survival [14]. Moreover, aberrant expression and constitutive activation of STAT3 have been detected in a variety of tumors such as the gastric cancer, breast cancer, prostate tumor, and NSCLC [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences revealed that the STAT3 was involved in the development and progression of many cancer types through participation in a series of tumorigenic processes such as cell proliferation and survival [14]. Moreover, aberrant expression and constitutive activation of STAT3 have been detected in a variety of tumors such as the gastric cancer, breast cancer, prostate tumor, and NSCLC [13][14][15]. Additionally, knockdown of STAT3 was proved to be facilitate to enhance the chemotherapy e cacy of malignant cancer by inhibition cell proliferation, invasion, and inhibition of drug-resistance [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies and a report from other groups have shown that STAT3 is a primary target of HJC0152 in breast cancer, head and neck squamous cell carcinoma, glioma, and gastric cancer . In this study, we showed that STAT3 expression is a prognostic factor for NSCLC patients (Figure A‐C), and that STAT3 is activated in NSCLC cells (Figure D and E).…”
Section: Resultssupporting
confidence: 74%
“…Interestingly, STA-21 slightly but significantly reduced ERK activity in MOLT-4 cells. It was recently reported that STAT3 inhibitor HJC0152 affected ERK activity in gastric cancer cells (20). Moreover, we found that STA-21 alone had no effect on levels of total and phosphorylated STAT3 protein in either cell line.…”
Section: Discussionsupporting
confidence: 44%